Project management information systems - a comparison study / Che Faridah Mat Taib and Royhaila Drahman - Mat Taib, Che Faridah; Drahman, Royhaila (2007)
This project is related to the application of project management information systems or PMISs for project management. PMIS is a tool to help the project manager in scheduling and controlling the project. A case study was used in the project to help evaluate the characterises among the different PMIS packages. The case study described the process for producing a hair lotion in an automated factory with the objective of having the product launched at a specific date. Three different types of PMIS were used to schedule the project. The packages that were used in the project were Microsoft Projects for Windows, Primavera and Artemis Project. The later two are Type 3 packages and Microsoft Project for Windows is a Type 2 package. After having used the different software on the case study, a better understanding of the features of Microsoft Project For Windows, Primavera and Artemis project was attained.